2009
DOI: 10.4141/cjps08142
|View full text |Cite
|
Sign up to set email alerts
|

Optimum leaf nutrient concentrations of wild lowbush blueberry in Quebec

Abstract: To evaluate the nutritional status of wild lowbush blueberry (Vaccinium angustifolium Ait.), optimum leaf nutrient concentrations were developed in earlier studies conducted in Canada's Maritime Provinces and in Maine. However, these concentrations have not been validated under the climatic and edaphic conditions of the Saguenay-Lac-Saint-Jean region of Quebec (Canada). These concentrations may not be necessarily correlated with the high productivity levels recorded in this region in recent years. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
0
22
1
2
Order By: Relevance
“…Cet effet du N sur ces e´le´ments a e´te´e´galement mesure´par Smagula et Ismail (1981). Les concentrations en N, en P, en K, en Ca et en Mg des feuilles ont atteint les valeurs des concentrations minimales pour combler les besoins de la culture qui sont de 16,36, 1,19, 5,40, 2,93 et 1,34 mg g (1 respectivement (Lafond 2009). Les apports fractionne´s de N ont eu un impact direct sur la nutrition de la culture en diminuant significativement les concentrations en N et en P des feuilles contrairement aux doses applique´es entie`rement au printemps de l'anne´e de ve´ge´tation (Tableaux 3 et 4).…”
Section: Nutrition Des Plantesunclassified
“…Cet effet du N sur ces e´le´ments a e´te´e´galement mesure´par Smagula et Ismail (1981). Les concentrations en N, en P, en K, en Ca et en Mg des feuilles ont atteint les valeurs des concentrations minimales pour combler les besoins de la culture qui sont de 16,36, 1,19, 5,40, 2,93 et 1,34 mg g (1 respectivement (Lafond 2009). Les apports fractionne´s de N ont eu un impact direct sur la nutrition de la culture en diminuant significativement les concentrations en N et en P des feuilles contrairement aux doses applique´es entie`rement au printemps de l'anne´e de ve´ge´tation (Tableaux 3 et 4).…”
Section: Nutrition Des Plantesunclassified
“…One of the main advantages of the proposed method is that the (frequently manual) removal of the non-border data is not required to then adjust the polynomial model in order to obtain the optimum concentration and sufficiency range, as observed by Lafond (2009) for N, P, K, Ca, and Mg.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluating the optimum concentration of N, P, K, Ca, and Mn in coniferous trees in Canada, Quesnel et al (2006) concluded that the method is considered appropriate for this purpose, similar to CND (compositional nutrient diagnosis). Similarly, Lafond (2009) obtained an optimum concentration and sufficiency range for N, P, K, Ca, and Mg of Vaccinium angustifolium, while Lenwandowski and Schmidt (2006) evaluated N efficiency of Tritico secale Wittmack, and Rafique et al (2008) used the method to assess the nutritional status of zinc in onion.…”
Section: Introductionmentioning
confidence: 99%
“…The boundary-line approach chosen by Lafond (2009) and proposed by Quesnel et al (2006) was used to determine the relationship between the micronutrients and yield. Briefly, this approach involved using various criteria to identify the maximum yield for all the micronutrients in order to cover all the measured concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…This approach was developed for biological data to establish a relationship between two variables measured under field conditions where the dependant variable is limited by more than one variable. As leaf blueberry nutrient concentrations vary greatly under the action of numerous environmental factors (Hall et al, 1982;Hepler and Yarborough, 1991;Trevett et al, 1968), this approach can be also suitable in blueberry production (Lafond, 2009 micronutrient concentrations in blueberry proposed previously are no longer necessarily suitable for the current crop productivity and for blueberry management methods. Moreover, minimum and maximum leaf concentrations were developed for blueberries grown under edaphic and climatic conditions different from those in the Saguenay-Lac-Saint-Jean region.…”
Section: Minimum and Maximum Leaf Micronutrient Concentrations In Wilmentioning
confidence: 96%